2013
DOI: 10.1038/npp.2013.123
|View full text |Cite
|
Sign up to set email alerts
|

Inferior Frontal Cortex Modulation with an Acute Dose of Heroin During Cognitive Control

Abstract: Impairments in inhibitory control and in stimulus-driven attention are hallmarks of drug addiction and are associated with decreased activation in the right inferior frontal gyrus (IFG). Although previous studies indicate that the response inhibition function is impaired in abstinent heroin dependents, and that this is mediated by reduced IFG activity, it remains completely unknown whether and how an acute dose of heroin modulates IFG activity during cognitive control in heroin-dependent patients. This study i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 50 publications
5
32
1
Order By: Relevance
“…In a recent study, we could show that heroin impairs stimulus-driven attention allocation, as indicated by reduced activity in the right inferior frontal gyrus (39). Further studies showed that loss of control over drug intake is not only a result of disrupted subcortical reward circuits but also of prefrontal higher-order executive functions (40).…”
Section: Discussionmentioning
confidence: 95%
“…In a recent study, we could show that heroin impairs stimulus-driven attention allocation, as indicated by reduced activity in the right inferior frontal gyrus (39). Further studies showed that loss of control over drug intake is not only a result of disrupted subcortical reward circuits but also of prefrontal higher-order executive functions (40).…”
Section: Discussionmentioning
confidence: 95%
“…However, most of the available data is focused on the role of a few frontal regions and of their connected subcortical structures, especially those of the corticobasal ganglia loop (Aron and Poldrack, 2006;Li et al, 2006;Schmidt et al, 2013;Vink et al, 2005). The suggested absence of any role for the parietal lobe, stemming from neurophysiological studies using the Go/No-Go task (Kalaska and Crammond, 1995), could be attributed to the fact that in successful trials of both tasks no movement is required and therefore, on the overall theoretical perspective (Scheme 1) adopted by this paper, on-line control/update of the movement trajectory is not required.…”
Section: Neurophysiological Studies In Animalsmentioning
confidence: 99%
“…More generally, our findings also contribute to a growing body of literature in which neuro imaging measures are used to evaluate the outcome of therapies for heroin addiction. 7,[30][31][32][33][34] The SN plays a role in salience detection and attention capture induced by error signals and dynamic cognitive control.…”
Section: Discussionmentioning
confidence: 99%